Pengaruh Financial Technology terhadap Peningkatan Pendapatan UMKM di Kabupaten Buleleng - Ni Putu Widhiani; Made Ary Meitriana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
This study aimed to examine the influence of financial technology on the income improvement of Micro, Small, and Medium Enterprises (MSMEs) in Buleleng Regency. A quantitative method with a descriptive approach was applied in this research. The population consisted of all trading-sector MSMEs in Buleleng Regency that had utilised financial technology services, totalling 204 business actors. A sample of 135 MSMEs was selected using purposive sampling. Data were collected through questionnaires and documentation. The questionnaire used a Likert scale and was tested for validity and reliability. Hypothesis testing was conducted using the t-test. The findings reveal that the use of financial technology has a positive and significant influence on the income of MSMEs. Easy access, transaction efficiency, and security offered by financial technology contribute meaningfully to business income growth. This indicates that the adoption of financial technology can be an effective strategy to support sustainability and competitiveness of MSMEs in the digital era.